Grupo de investigación Emergencias y Desastres - Forero Pulido, Constanza; Pérez Peláez, Liria; Hincapié, María Cecilia; Betancur Taborda, Ceneida; Mejía Londoño, María Eugenia; Quintero Tobón, María Teresa; Varela Londoño, Luz Estela; Pineda Cadavid, Gladys Elena; Gutiérrez, Natalia Ángel; Cano Hoyos, Johana Andrea (Investigación y Educación en Enfermería, 2013)
.